2015
DOI: 10.1016/j.jvs.2014.12.038
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of medically managed acute type B aortic dissection

Abstract: The majority of patients with acute type B dissection will fail medical therapy over time as evidenced by a 6-year intervention-free survival of 41%. Patients who underwent any aortic intervention had a significant survival advantage over those who were treated with medical management alone. Further study is necessary to determine who will benefit most from early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
100
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(108 citation statements)
references
References 31 publications
4
100
4
Order By: Relevance
“…In our study, the early event rate in the TEVAR group was 10.3%, which was higher than that of the BMT group (4.5%), although the difference was not statistically significant. The early event rate in the BMT group was consistent with findings from previous studies (19,20 In previous studies, the early mortality rates in patients with type B aortic dissection treated with TEVAR range between 2.4% and 10.9% (8,14) and, in patients treated with BMT, the range has been between 0% and 10.6% (5,11,21,22 CTA imaging in this study. Consistent with an earlier report (23), SINE was a severe complication in the TEVAR group and was associated with substantial mortality The patients in the BMT group experienced more aortic-related adverse events than those treated with TEVAR (Figure 1), and this result was partially consistent with our earlier report (11).…”
Section: Resultssupporting
confidence: 91%
“…In our study, the early event rate in the TEVAR group was 10.3%, which was higher than that of the BMT group (4.5%), although the difference was not statistically significant. The early event rate in the BMT group was consistent with findings from previous studies (19,20 In previous studies, the early mortality rates in patients with type B aortic dissection treated with TEVAR range between 2.4% and 10.9% (8,14) and, in patients treated with BMT, the range has been between 0% and 10.6% (5,11,21,22 CTA imaging in this study. Consistent with an earlier report (23), SINE was a severe complication in the TEVAR group and was associated with substantial mortality The patients in the BMT group experienced more aortic-related adverse events than those treated with TEVAR (Figure 1), and this result was partially consistent with our earlier report (11).…”
Section: Resultssupporting
confidence: 91%
“…We previously showed that the 6-year intervention-free survival of patients with acute type B dissection treated with medical therapy alone is 40%. 11 Accordingly, many patients may benefit from early thoracic stent grafting. However, criteria to determine appropriate patient selection and the exact timing of the early intervention remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…5,[7][8][9][10] We recently showed in a contemporary series of patients that aneurysmal degeneration of the aorta has been relatively unaltered by current medical therapy, because only 41% of patients demonstrated an intervention-free survival after 6 years. 11 However, there are limited contemporary data regarding the rate of aortic expansion while patients are being managed with optimal medical therapy, and there is a paucity of data regarding which factors might be predictive of aortic growth. The goal of this study was to evaluate the rate of aneurysmal degeneration in a contemporary series of patients with acute type B aortic dissection who were initially treated with medical therapy alone and to identify factors associated with aortic growth.…”
mentioning
confidence: 99%
“…Up to 40% of patients reportedly undergo surgery after BMT, resulting in a relatively low overall 6-year interventionfree survival rate approximating 41% (5-7). Furthermore, the reported 3-, 5-, and 6-year mortality rates are also suboptimal at 22.4%, 27.9%, and 42%, respectively (7)(8)(9).…”
mentioning
confidence: 96%